Method for preparing electrochromic device by electrodepositing prussian white through electrochemical treatment

By using a three-electrode system in electrochemical deposition to convert Prussian blue into Prussian white and assembled with PEDOT:PSS electrodes, the problem of valence state fixation of electrochromic materials is solved, and the discoloration performance and stability of electrochromic devices are improved.

CN119710856APending Publication Date: 2025-03-28SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510088310.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The electrochromic materials prepared by the existing electrochemical deposition methods are fixed in valence state, making it difficult to enhance the electrochromic performance without destroying the structure.

Method used

Using a three-electrode system and organic electrolyte, Prussian blue is converted to Prussian white, and PEDOT:PSS electrode is prepared by screen printing and assembled into a flexible electrochromic device.

Benefits of technology

Improves the color discoloration performance and cycling stability of electrochromic devices, enables higher color contrast at lower applied voltages, and maintains the flexibility of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710856A_ABST
    Figure CN119710856A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochromic devices and electrochemistry, and particularly relates to a method for preparing an electrochromic device through electrochemical treatment and electrodeposition of Prussian white. The organic electrolyte with a higher electrochemical window is used, the three-electrode system is used for converting the Prussian blue into the Prussian white, then the color changing performance of the electrochromic device is enhanced, the cycling stability is excellent, and the performance of the Prussian blue obtained through the electrochemical deposition mode is not damaged. Meanwhile, by designing complementary electrochromic devices, namely, electrochemically treated Prussian white and silk-screen printed PEDOT: PSS serve as complementary electrochromic materials, the electrochromic performance and stability are further enhanced. Besides, no matter whether the electrochromic device is rigid (FTO glass) or flexible (ITO-PET), the performance of the electrochromic device can be ensured to be relatively consistent by using the same preparation process, so that the device can be flexible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochromic devices and electrochemical technology, and in particular relates to a method for preparing an electrochromic device by electrochemically treating and electrodepositing Prussian white. Background Art

[0002] The field of electrochromic devices is one of the emerging technology fields in recent years. As a new generation of energy-saving devices, it has great application potential in smart windows, energy-saving displays, etc. Since Deb discovered the electrochromic properties of tungsten oxide in the last century, various electrochromic materials have been explored and applied. In addition to the most important electrochromic materials, the typical structure of an electrochromic device also includes electrolytes, ion storage layers and electrode materials. The electrochromic material is mainly responsible for the color change of the device, the electrolyte layer is mainly responsible for the ion transport of the device under an external electric field, and the ion storage layer is responsible for storing the ions transferred by the electrochemical reaction of the electrochromic material. The electrode layer is directly connected to the external circuit to provide a potential difference for the entire device. Such a multi-layer structure leads to varying degrees of difficulty in the preparation and assembly of different functional layers of electrochromic devices.

[0003] Electrochemical deposition is a common method for preparing electrochromic materials. It has the advantages of simple synthesis and good stability, but its electrochromic performance cannot be guaranteed. On the one hand, the structure of electrochemically deposited electrochromic materials is relatively compact, and the rate of ion insertion and extraction is often limited; on the other hand, the valence state of electrochromic materials obtained by electrochemical deposition is often fixed. In order to enhance the performance of electrochromic devices, it is often necessary to perform a valence state transformation treatment on the electrochemically deposited electrochromic materials before assembling the devices. This treatment often corresponds to a color change. However, changing the valence state of electrochemically deposited electrochromic materials by using chemical methods such as oxidants or reductants often destroys the structure of the electrochromic materials, and the reaction conditions may be more demanding.

[0004] As mentioned above, electrochemical deposition provides a simple method to make a close connection between electrochromic materials and electrodes, and allows electrochromic materials to be synthesized in situ in the electrode layer. However, since its synthesis requires an external electric field, the valence state of the obtained product is often fixed. Therefore, how to make the electrochemically deposited electrochromic material present the most suitable valence state for electrochromism without destroying its original stability has become one of the problems that need to be solved in the field of electrochemical deposition. Summary of the invention

[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a method for preparing a flexible electrochromic device by electrochemically treating and electrodepositing Prussian white, which utilizes a three-electrode system and an organic electrolyte to convert Prussian blue into Prussian white to enhance the electrochromic performance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a method for preparing an electrochromic device by electrochemically treating and electrodepositing Prussian white, the method comprising the following steps:

[0008] S1. Electrochemical deposition of Prussian blue: using an aqueous solution containing potassium chloride, ferric oxide and potassium ferrocyanate as an electrolyte, electrochemically depositing Prussian blue on ITO glass or ITO film or FTO glass;

[0009] S2, treating Prussian blue to Prussian white: converting electrochemically deposited Prussian blue to Prussian white in an organic electrolyte containing an organic lithium salt under a three-electrode system to prepare a Prussian white electrode;

[0010] S3, screen printing PEDOT:PSS: PEDOT:PSS electrodes are made by screen printing using PEDOT:PSS ink on ITO glass or ITO film or FTO glass;

[0011] S4, assembling an electrochromic device: assembling the Prussian white electrode of step S2 and the PEDOT:PSS electrode of step S3 into an electrochromic device, and then injecting a curable electrolyte between the Prussian white electrode and the PEDOT:PSS electrode, and obtaining the electrochromic device after curing.

[0012] The present invention utilizes a three-electrode system to convert Prussian blue into Prussian white to enhance electrochromic performance. Prussian blue is a compound with multiple valence states, which is arranged from a completely reduced state to a completely oxidized state, and is white, blue and yellow-green, respectively. Generally, Prussian blue deposited by constant potential is blue, and blue is an intermediate valence state. The voltage required for its complete oxidation to yellow-green is higher, while the voltage required for oxidation from white to blue is lower, and the color contrast is higher. Therefore, under a lower applied voltage, using Prussian white as an electrochromic electrode is more effective, and utilizing a three-electrode system to process is a simple method for converting Prussian blue into Prussian white. At the same time, when converting Prussian blue into Prussian white under a three-electrode system, the electrolyte system used is an organic electrolyte, rather than an aqueous electrolyte. The reason may be that the organic electrolyte has a higher electrochemical window, and the reaction is milder under the same voltage conditions, and the structure of the deposited Prussian blue or Prussian white will not be destroyed.

[0013] Preferably, the sheet resistance of the ITO glass or ITO film or FTO glass is 10 to 50 ohms.

[0014] Preferably, the electrolyte described in S1 is an aqueous solution containing 0.05-0.5 mol / L potassium chloride, 0.01-0.05 mol / L ferric oxide and 0.01-0.05 mol / L potassium ferrocyanate.

[0015] Preferably, the organic electrolyte in S2 comprises an organic solvent and an organic lithium salt, the organic solvent is at least one of propylene carbonate (PC), ethylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), and the organic lithium salt is at least one of lithium borate oxalate (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0016] Preferably, S2 processes Prussian blue into Prussian white by constant potential method, with a voltage of -0.3V to -0.7V and a time of 70-100s.

[0017] Preferably, the three-electrode system described in S2 uses Prussian blue as the working electrode, a platinum wire electrode as the counter electrode, and a silver-silver chloride electrode as the reference electrode.

[0018] Preferably, the mesh number of the screen used for S3 screen printing PEDOT:PSS is 200-400 meshes.

[0019] Preferably, the curable electrolyte in S4 contains the same organic lithium salt as the organic electrolyte in S2.

[0020] Preferably, the curable electrolyte of S4 is a photocurable electrolyte, specifically a mixed solution of propylene carbonate, acryloyl morpholine and an organic lithium salt, with a mass ratio of 9-11:3-5:2-4; based on the molar fraction of acryloyl morpholine, it also contains 1-2% of a photoinitiator and 1,6-hexanediol diacrylate, respectively.

[0021] Preferably, the electrodeposition method described in S1 includes a constant current method and a pulse potential method.

[0022] Preferably, the ITO glass or ITO film or FTO glass is cleaned with water and ethanol before use.

[0023] The second aspect of the present invention provides an electrochromic device prepared by the method described in the first aspect.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention discloses a method for preparing a flexible electrochromic device by electrochemically treating and electrodepositing Prussian white. By using an organic electrolyte with a higher electrochemical window (compared with an aqueous electrolyte), a three-electrode system is used to convert Prussian blue into Prussian white, thereby enhancing the color change performance of the electrochromic device, and the cycle stability is excellent. The performance of the Prussian blue obtained by this electrochemical deposition method is not destroyed. At the same time, the present invention further enhances the electrochromic performance and stability by designing complementary electrochromic devices, that is, electrochemically treated Prussian white and screen-printed PEDOT:PSS as complementary electrochromic materials. In addition, the preparation of flexible electrochromic devices has always been a hot branch in the field of electrochromism, but the color change effect of flexible devices prepared by copying the preparation method of rigid electrochromic devices is often greatly reduced. The electrochromic device described in the present invention, whether rigid (FTO glass) or flexible (ITO-PET), uses the same preparation process, and its performance can be guaranteed to be relatively consistent, indicating that the device described in the present invention can be flexible.

[0026] In the electrochromic device of the present invention, the preparation process of the Prussian white layer is simple and will not damage the cycle stability of the device. Compared with the device assembled directly using Prussian blue, the electrochromic performance is more excellent. In addition, the device can also be prepared as a flexible device without changing the process flow. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 CV curve of PB in a three-electrode system of 0.5 M KCl aqueous solution before cycling;

[0028] Figure 2 CV curve of PB after cycling in a three-electrode system with 0.5 M KCl aqueous solution;

[0029] Figure 3 CV curve of PB in a three-electrode system containing 1 M LiTFSIPC solution before cycling;

[0030] Figure 4 CV curve of PB after cycling in a three-electrode system containing 1 M LiTFSIPC solution;

[0031] Figure 5 is a structural diagram of an electrochromic device;

[0032] Figure 6 Transmittance changes of Prussian white-PEDOT:PSS device with FTO glass in the colored and faded states;

[0033] Figure 7 Cyclic stability of Prussian white-PEDOT:PSS device on FTO glass at 620nm wavelength;

[0034] Figure 8 Transmittance changes of Prussian blue-PEDOT:PSS device with FTO glass in the colored and faded states;

[0035] Fig. 9 Comparison of optical modulation between Prussian blue-PEDOT:PSS electrochromic device on FTO glass and Prussian blue-PEDOT:PSS electrochromic device on FTO glass;

[0036] Fig.10 The transmittance change of Prussian blue-PEDOT:PSS device of ITO-PET in the colored state and faded state;

[0037] Fig.11 Cycling stability of Prussian white-PEDOT:PSS device with ITO-PET at 620nm wavelength. DETAILED DESCRIPTION

[0038] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0039] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0040] Example 1: Comparison of the cyclic stability of Prussian blue in aqueous electrolyte and in organic electrolyte

[0041] (1) Pretreatment of FTO glass: 2 The FTO glass (square resistance of 15Ω) was ultrasonically cleaned in water and anhydrous ethanol for 10 minutes respectively, and dried for use.

[0042] (2) Electrochemical deposition of Prussian blue: Prussian blue was deposited on FTO glass by constant potential method at 0.5 V for 30 seconds under a three-electrode system. The area of ​​the deposited part was 5×5 cm 2 The electrolyte is an aqueous solution containing 0.01 mol / L potassium ferrocyanide, 0.02 mol / L ferric chloride, and 0.1 mol / L potassium chloride; in the three-electrode system, the working electrode is FTO glass, the counter electrode is a platinum wire electrode, and the reference electrode is a silver-silver chloride electrode. After the deposition is completed, the Prussian blue-FTO glass is repeatedly rinsed with pure water, and then placed in a 60°C oven for drying.

[0043] (3) Stability test of Prussian blue-FTO glass in aqueous electrolyte: The aqueous electrolyte used is an aqueous solution containing 0.5 mol / L potassium chloride, with Prussian blue-FTO glass as the working electrode, platinum electrode as the counter electrode, and silver chloride as the reference electrode to form a three-electrode system. The specific operation of the stability test is: respectively at -0.5V, 0V, 0.5V, 1V, and 1.5V for 200s to allow the Prussian blue-FTO glass to complete a thorough ion embedding-ex-embedding process, and then test the cyclic voltammetry curves before and after the stability test. The results are as follows: Figure 1 and Figure 2 As shown. The scanning speed of the cyclic voltammetry curve is 50mV / s, and the scanning voltage range is -0.5~1.5V. The results show that the peak current of the CV curve and the area enclosed by the curve (the amount of charge embedded in the Prussian blue-FTO glass) before and after the cycle are reduced, and the shape of the curve is also changed, indicating that the structure of the electrochemically deposited Prussian blue material is destroyed.

[0044] (4) Stability test of Prussian blue-FTO glass in organic electrolyte: The organic electrolyte used was a propylene carbonate (PC) solution containing 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). Except for the different electrolyte composition, the rest of the operation was exactly the same as step (3), and the cyclic voltammetry curves before and after the stability test were also obtained. The results are shown in Figure 2. Figure 3 and Figure 4 The results show that the peak current of the CV curve before and after the cycle is relatively unchanged, and the curve morphology remains stable, indicating that the structure of the electrochemically deposited Prussian blue material is not destroyed after cycling in the 1M LiTFSI PC solution.

[0045] This example shows that the prepared Prussian blue-FTO glass is more stable in an organic electrolyte system than in an aqueous electrolyte system, which lays an experimental foundation for using organic electrolyte to prepare Prussian white.

[0046] Example 2: Preparation of Prussian White-PEDOT:PSS electrochromic device of FTO glass

[0047] (1) Pretreatment of FTO glass: 2 The FTO glass (square resistance of 15Ω) was ultrasonically cleaned in water and anhydrous ethanol for 10 minutes respectively, and dried for use.

[0048] (2) Electrochemical deposition of Prussian blue: Prussian blue was deposited on FTO glass by constant potential method at 0.5 V for 30 seconds under a three-electrode system. The area of ​​the deposited part was 5×5 cm 2The electrolyte is an aqueous solution containing 0.01 mol / L potassium ferrocyanide, 0.02 mol / L ferric chloride, and 0.1 mol / L potassium chloride; in the three-electrode system, the working electrode is FTO glass, the counter electrode is a platinum wire electrode, and the reference electrode is a silver-silver chloride electrode. After the deposition is completed, the Prussian blue-FTO glass is repeatedly rinsed with pure water, and then placed in a 60°C oven for drying.

[0049] (3) Converting the electrochemically deposited Prussian blue into Prussian white: Treat the Prussian blue-FTO glass obtained in step (2) at a voltage of -0.5 V for 90 seconds in a three-electrode system by a constant potential method to obtain Prussian white-FTO glass. The electrolyte is a propylene carbonate (PC) solution containing 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). The working electrode is the Prussian blue-FTO glass, the counter electrode is a platinum wire electrode, and the reference electrode is a silver-silver chloride electrode. After the treatment is completed, dry it at room temperature for use.

[0050] (4) Screen printing PEDOT:PSS: The purchased PEDOT:PSS ink was directly screen printed on the FTO glass, where the screen printed pattern was 5×5 cm 2 The screen was 250 mesh. After screen printing, the PEDOT:PSS-FTO glass was placed at room temperature for 5 minutes, then transferred to an oven at 80°C for annealing for 10 minutes, and then taken out for use.

[0051] (5) Assembly of FTO glass Prussian white-PEDOT:PSS electrochromic device: Prussian white-FTO glass and PEDOT:PSS-FTO glass were assembled as follows: Figure 5 Assembled in the manner shown, a U-shaped silicone rubber is sandwiched between the two layers as a template for pouring a curable electrolyte. The curable electrolyte is poured into the gap of the silicone rubber and cured for 30 seconds under ultraviolet light with a wavelength of 365nm to obtain an electrochromic device. Among them, the components of the curable electrolyte used are: a mixed solution of propylene carbonate, acryloylmorpholine and lithium bis(trifluoromethylsulfonyl)imide, with a mass ratio of 10:4:3, and also contain 1% (in terms of molar fraction of acryloylmorpholine) of photoinitiator 184 and 1,6-hexanediol diacrylate. The above components are mixed together and magnetically stirred until uniform to obtain a curable electrolyte.

[0052] (6) Test of the color-changing performance of FTO glass electrochromic device: With Prussian white-FTO glass as the positive electrode and PEDOT:PSS-FTO glass as the negative electrode, an external voltage of 1.5V was applied for 60 seconds to test the device's colored transmittance, and then an external voltage of -0.5V was applied for 60 seconds to test the device's faded transmittance. The wavelength range of the test transmittance is 400-800nm. The test results are as follows: Figure 6 As shown, the test results show that in most visible light bands, the transmittance difference between the colored state and the faded state of the device is greater than 10%. In the 600-700nm band, the change in transmittance is basically greater than 20%, indicating that the electrochromic device has a good color-changing effect.

[0053] (7) Cyclic stability test of FTO glass electrochromic device: The positive and negative electrodes are the same as in step (6), the coloring voltage is 1.5V, the fading voltage is -0.5V, each lasts for 30s, and the cycle is repeated 200 times to test the cyclic stability of the device. The test wavelength is 620nm, and the test results are as follows: Figure 7 This indicates that the device has good cycle stability.

[0054] Comparative Example 1: Preparation of Prussian Blue-PEDOT:PSS Electrochromic Device on FTO Glass

[0055] Compared with Example 1, except that step (3) in Example 1 is not included, the preparation process of the device is the same, and the specific preparation process is as follows:

[0056] (1) Pretreatment of FTO glass: 2 The FTO glass (square resistance of 15Ω) was ultrasonically cleaned in water and anhydrous ethanol for 10 minutes respectively, and dried for use.

[0057] (2) Electrochemical deposition of Prussian blue: Prussian blue was deposited on FTO glass by constant potential method at 0.5 V for 30 seconds under a three-electrode system. The area of ​​the deposited part was 5×5 cm 2 The electrolyte is an aqueous solution containing 0.01 mol / L potassium ferrocyanide, 0.02 mol / L ferric chloride, and 0.1 mol / L potassium chloride; in the three-electrode system, the working electrode is FTO glass, the counter electrode is a platinum wire electrode, and the reference electrode is a silver-silver chloride electrode. After the deposition is completed, the Prussian blue-FTO glass is repeatedly rinsed with pure water, and then placed in a 60°C oven for drying.

[0058] (3) Screen printing PEDOT:PSS: The purchased PEDOT:PSS ink was directly screen printed on the FTO glass, where the screen printed pattern was 5×5 cm 2The screen was 250 mesh. After screen printing, the PEDOT:PSS-FTO glass was placed at room temperature for 5 minutes, then transferred to an oven at 80°C for annealing for 10 minutes, and then taken out for use.

[0059] (4) Assembly of Prussian blue-PEDOT:PSS electrochromic device of FTO glass: Prussian blue-FTO glass and PEDOT:PSS-FTO glass were assembled as follows: Figure 5 Assembled in the manner shown, a U-shaped silicone rubber is sandwiched between the two layers as a template for pouring a curable electrolyte. The curable electrolyte is poured into the gap of the silicone rubber and cured for 30 seconds under ultraviolet light with a wavelength of 365nm to obtain an electrochromic device. Among them, the components of the curable electrolyte used are: a mixed solution of propylene carbonate, acryloylmorpholine and lithium bis(trifluoromethylsulfonyl)imide, with a mass ratio of 10:4:3, and also contain 1% (in terms of molar fraction of acryloylmorpholine) of photoinitiator 184 and 1,6-hexanediol diacrylate. The above components are mixed together and magnetically stirred until uniform to obtain a curable electrolyte.

[0060] (5) Test of the color change performance of FTO glass electrochromic device: With Prussian blue-FTO glass as the positive electrode and PEDOT:PSS-FTO glass as the negative electrode, an external voltage of 1.5V was applied for 60 seconds to test the device's colored transmittance, and then an external voltage of -0.5V was applied for 60 seconds to test the device's faded transmittance. The wavelength range of the test transmittance was 400-800nm. The test results are as follows: Figure 8 As shown in the figure, the test results show that in most visible light bands, the transmittance difference between the colored state and the faded state of the device is about 10%. The optical modulation comparison of the FTO glass Prussian white-PEDOT:PSS electrochromic device and the FTO glass Prussian blue-PEDOT:PSS electrochromic device (the difference between the transmittance of the faded state and the transmittance of the colored state) is shown in the figure. Fig. 9 As shown, it can be seen that in the visible light wavelength range of 400 to 500 nm, the optical modulation of the Prussian blue-PEDOT:PSS electrochromic device is equivalent to that of the Prussian white-PEDOT:PSS electrochromic device, while in the wavelength range of 500 to 800 nm, the optical modulation of the Prussian white-PEDOT:PSS electrochromic device is significantly higher than that of the Prussian blue-PEDOT:PSS electrochromic device.

[0061] Compared with Example 1, Comparative Example 1 highlights that the device described in Example 1 has better electrochromic performance.

[0062] Comparative Example 2: Preparation of Flexible Electrochromic Device

[0063] Compared with Example 1, except that the FTO glass is replaced by an ITO-PET film (square resistance 10Ω), the preparation process of the device is the same, and finally a flexible electrochromic device is prepared.

[0064] The transmission spectra of the flexible electrochromic device in the colored and faded states, as well as its cyclic stability at a wavelength of 620nm, were also tested. The test results are as follows: Fig.10 and Fig.11 As shown, the test results of the flexible device show that its transmittance changes and cycle stability in the colored and faded states are similar to the device performance of FTO glass, indicating that the same preparation process can be applied to both flexible and rigid devices.

[0065] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing an electrochromic device by electrochemical treatment of electrodeposited Prussian white, characterized in that: The following steps are involved: S1. Electrochemical deposition of Prussian blue: using an aqueous solution containing potassium chloride, ferric oxide and potassium ferrocyanate as an electrolyte, electrochemically depositing Prussian blue on ITO glass or ITO film or FTO glass; S2, treating Prussian blue to Prussian white: converting electrochemically deposited Prussian blue to Prussian white in an organic electrolyte containing an organic lithium salt under a three-electrode system to prepare a Prussian white electrode; S3, screen printing PEDOT:PSS: PEDOT:PSS electrodes are made by screen printing using PEDOT:PSS ink on ITO glass or ITO film or FTO glass; S4, assembling an electrochromic device: assembling the Prussian white electrode of step S2 and the PEDOT:PSS electrode of step S3 into an electrochromic device, and then injecting a curable electrolyte between the Prussian white electrode and the PEDOT:PSS electrode, and obtaining the electrochromic device after curing.

2. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: The sheet resistance of the ITO glass or ITO film or FTO glass is 10 to 50 ohms.

3. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: The electrolyte described in S1 is an aqueous solution containing 0.05-0.5 mol / L potassium chloride, 0.01-0.05 mol / L ferric oxide and 0.01-0.05 mol / L potassium ferrocyanate.

4. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: S2 The organic electrolyte includes an organic solvent and an organic lithium salt, the organic solvent is at least one of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate, and the organic lithium salt is at least one of lithium borate oxalate, lithium difluorooxalate borate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

5. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: S2 treated Prussian blue to Prussian white by constant potential method, the voltage was -0.3V~-0.7V, and the time was 70-100s.

6. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: The three-electrode system described in S2 uses Prussian blue as the working electrode, a platinum wire electrode as the counter electrode, and a silver-silver chloride electrode as the reference electrode.

7. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: The mesh number of the screen used for S3 screen printing PEDOT:PSS is 200-400 mesh.

8. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 1, characterized in that: The curable electrolyte of S4 contains the same organic lithium salt as the organic electrolyte of S2.

9. The method for preparing an electrochromic device by electrochemical treatment and electrodeposition of Prussian white according to claim 8, characterized in that: The curable electrolyte of S4 is a photocurable electrolyte, specifically a mixed solution of propylene carbonate, acryloyl morpholine and organic lithium salt, with a mass ratio of 9-11:3-5:2-4; based on the molar fraction of acryloyl morpholine, it also contains 1-2% of photoinitiator and 1,6-hexanediol diacrylate.

10. An electrochromic device prepared by the method according to any one of claims 1 to 9.